Insuficiencia cardíaca con fracción de eyección intermedia: ¿Dos entidades superpuestas? - Martín-Sánchez, F. Javier; Angós, Beatriz; Bajo Cardassay, Eduardo; Rodríguez Adrada, Esther (CorSalud, 2019)
Insuficiencia cardíaca con fracción de eyección intermedia: ¿Dos entidades superpuestas?